DEVELOPMENT OF A COMBINED METHOD FOR FORECASTING ELECTRICITY CONSUMPTION OF AN INDUSTRIAL ENTERPRISE LLC EVROSNAR - Jahongir Davronov (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: The scientific article discusses methods to improve the accuracy of forecasting electricity consumption by industrial enterprises on the example of the company Evrosnar. The influence of weather conditions on the accuracy of forecasting is analyzed.